Ulcerative Colitis Narrative findings: Australian survey data comparing patient and physician disease management views. Issue 9 (14th August 2021) - Connor, Susan J.; Sechi, Alexandra; Andrade, Mauricio; Deuring, J. Jasper; Witcombe, David
Abstract: Background and Aim: The Global Ulcerative Colitis (UC) Narrative Survey aimed to evaluate the impact of UC, perceptions of UC burden, and management approaches. Here, we present data from patients and physicians in Australia. Methods: Surveys, fielded by The Harris Poll, were completed by 215 patients with UC and 90 physicians, between August 2017 and February 2018. Surveys included questions on disease characteristics, impact on life, communication with physicians, and patient knowledge of UC. Results are presented descriptively from all respondents (with no imputation for missing data). Results: Based on medication history, 84% of patients had moderate to severe UC. Diagnostic delay was on average 1.9 (SD 5.0) years and 48% of patients had waited ≥1 year for diagnosis. Nearly two‐thirds (65%) of patients considered themselves to be in remission, with 97% also reporting a flare in the past year. The majority (92%) of patients were satisfied with their UC medication and, if their treatment made them feel "good enough, " many (75%) would not consider an alternative. Most (90%) patients were satisfied with communication with their physician; however, only 48% felt comfortable raising emotional concerns. Both patients and physicians desired more time during routine appointments. Patients had gaps in their knowledge of UC, which physicians mostly recognized. Conclusions: The Australian survey results highlighted the diagnostic delay and burden of UC patients' experience, gaps in patients' knowledge of UC, and challenges in patient–physician communication. Compared with the overall Global UC Narrative Survey, patients in Australia reported a high burden of disease. Abstract : The Australia‐specific patient and physician results from the Global Ulcerative Colitis Narrative Survey are reported; they highlight a high disease burden, problems of diagnostic delay, and challenges in patient–physician communication. Pfizer Inc funded editorial support and the study.